A new role for microRNA pathways: modulation of degeneration induced by pathogenic human disease proteins. - Bilen, J.; Liu, N.; Bonini, N.M. (Cell Cycle, 2006)
MicroRNAs (miRNAs) are small noncoding RNAs that regulate the expression of target transcript mRNAs. Many miRNAs have been defined, however their roles and the processes influenced by miRNA pathways are still being elucidated. A role for miRNAs in development and cancer has been described. We recently isolated the miRNA bantam (ban) in a genetic screen for modulators of pathogenicity of a human neurodegenerative disease model in Drosophila. These studies showed that upregulation of ban mitigates degeneration induced by the pathogenic polyglutamine (polyQ) protein Ataxin-3, which is mutated in the human polyglutamine disease spinocerebellar ataxia type 3 (SCA3). To address the broader role for miRNAs in neuroprotection, we also showed that loss of all miRNAs, by dicer mutation, dramatically enhances pathogenic polyQ protein toxicity in flies and in human HeLa cells. These studies suggest that miRNAs may be important for neuronal survival in the context of human neurodegenerative disease. These studies provide the foundation to define the miRNAs involved in neurodegenerative disease, and the biological pathways affected.